Kinetics of CD4+ T-Lymphocyte in Dengue Virus Infection - Laksono, Ida Safitri; Intansari, Umi S. (Faculty of Medicine, Universitas Padjadjaran, 2014)
Cellular immunity plays an important role in viral infection. The activation of effector T-lymphocytes and the release of cytokines define the course of dengue viral infection. CD4âº T-lymphocyte induces the immunopathology via various mechanisms; however, Â its kinetics in different onset of fever and disease severity are not fully understood. This study was conducted to observe the kinetics of CD4+ T-lymphocyte level among dengue infected patients and to obtain the absolute cell count and relative percentage of CD4+ T-lymphocyte. This was a descriptive study on thirty six patients who met the WHO-1997 criteria of dengue infection, hospitalized in Dr. Sardjito Hospital in the period of March to May 2009. The CD4+ T-lymphocytes were examined using the flow cytometer. The significance of median CD4+ T-lymphocytes among days were assessed using Kruskal-Wallis and Mann-Whitney SPSS 11 for Window. The absolute CD4+ T-lymphocyte was significantly different among days (p<0.05) between DF and DHF patients, while the relative CD4+ percentage count was notÂ different (p>0.05).Â The Absolute CD4+ T-lymphocytes count was low in the beginning of the disease course and increased from the 2nd day of fever to the normal level on the 7th day. In conclusion, DF and DHF do not differ in the absolute CD4+ T-lymphocytes count as well as in the relative CD4+ T-lymphocytes percentage.Key words: CD4+ T-lymphocyte, dengue fever, dengue hemorrhagic fever, dengue virusKinetik Limfosit T CD4+ pada infeksi Virus DengueAbstrakImunitas seluler berperan penting dalam infeksi virus. Aktivasi efektor limfosit T dan terlepasnya sitokin merupakan gambaran utama perjalanan klinis infeksi virus dengue. Sel limfosit T CD4+ menginduksi imunopatologi melalui berbagai mekanisme, namun bagaimana kinetikanya pada hari demam yang berbeda dan derajat berat penyakit masih belum sepenuhnya dipahami. Penelitian ini bertujuan untuk mengamati kinetika sel limfosit T CD4+ pada pasien infeksi dengue dan mendapatkan kadar absolut serta persentase relatif limfosit T CD4+. Penelitian deskriptif ini mengikutsertakan tiga puluh enam pasien yang memenuhi kriteria WHO 1997 untuk infeksi dengue, dirawat di RSUP Dr. Sardjito antara Maret sampai Mei 2009. Kadar limfosit T CD4+ diperiksa menggunakan flow cytometer. Perbedaan median limfosit T CD4+ pada berbagai hari demam dianalisis menggunakan Uji Kruskal-Wallis dan Mann-Whitney SPSS 11 untuk Windows. Kadar absolut limfosit T CD4+ berbeda secara bermakna antara hari demam (p<0,05). Persentase relatif limfosit T CD4+ tidak berbeda bermakna antara demam dengue dan demam berdarah dengue (p>0,05). Kadar absolut limfosit T CD4+ rendah pada awal perjalanan penyakit, meningkat pada hari ke-2 demam dan mencapai nilai normal pada hari ke-7 demam. Demam dengue dan demam berdarah dengue tidak menunjukkan kadar absolut maupun persentase relatif limfosit T CD4+ yang berbeda bermakna. Kata kunci: Demam berdarah dengue, demam dengue, limfosit T CD4+, virus dengueÂ DOI: 10.15395/mkb.v46n4.341